Great mimicker – a case of occult melanoma displaying ganglioneuroblastic differentiation - Skrzypkowska, Paulina; Kunc, Michał; Biernat, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2023)
Melanomas are known for their diverse morphological features, presenting a diagnostic challenge for pathologists. Uncommon variations of melanoma can exhibit distinct cytological and histomorphological characteristics, including ganglioneuroblastic differentiation. However, this phenomenon is extremely rare, with only a few documented cases. Here, we present a unique case of an occult metastatic melanoma with ganglioneuroblastic differentiation developing in a 76-year-old male. The diagnosis was based on histopathology, immunophenotyping, and molecular testing, which revealed SOX10 positivity and an NRAS mutation. Notably, classic melanoma markers HMB45 and melan-A were negative, highlighting the importance of considering alternative markers. This case emphasizes the significance of immunohistochemistry and molecular investigation in diagnosing melanomas with unusual features and identifying appropriate candidates for immune checkpoint therapy. Additionally, the occurrence of ganglioneuroblastic differentiation further supports a shared histogenetic origin from the neural crest. Improved understanding of such rare variants contributes to accurate diagnosis and optimal management of melanoma patients.